Heart Caring "Handy" - Prototype - Retnasamy, Vithyacharan (Malaysian Invention and Design Society (MINDS), 2010)
R. Charan and his team won bronze for Heart Caring "Handy" - Prototype at ITEX 2006, 19th - 21st May 2006 at Kuala Lumpur Convention Centre (KLCC), Kuala Lumpur.